2019
DOI: 10.1007/s13311-018-0663-y
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Removal of False Connections in Diffusion MRI Tractography Using Topology-Informed Pruning (TIP)

Abstract: Diffusion MRI fiber tracking provides a non-invasive method for mapping the trajectories of human brain connections, but its false connection problem has been a major challenge. This study introduces topology-informed pruning (TIP), a method that automatically identifies singular tracts and eliminates them to improve the tracking accuracy. The accuracy of the tractography with and without TIP was evaluated by a team of 6 neuroanatomists in a blinded setting to examine whether TIP could improve the accuracy. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
100
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 144 publications
(101 citation statements)
references
References 16 publications
0
100
0
1
Order By: Relevance
“…Unlike most other diffusion metrics, RDI does does not depend on an underlying diffusion model or numerical optimization to estimate model parameters, making it easily applicable to a wider range of databases and clinical scanner protocols. RDI’s sensitivity to cell density has been useful in differentiating tissue in patients with tumors 44, 45 , as well as measuring therapeutic benefits of deep brain stimulation 46 . In a phantom study by Yeh et al, the optimized restricted diffusion showed an almost perfect correlation of 0.998 with cell density 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Unlike most other diffusion metrics, RDI does does not depend on an underlying diffusion model or numerical optimization to estimate model parameters, making it easily applicable to a wider range of databases and clinical scanner protocols. RDI’s sensitivity to cell density has been useful in differentiating tissue in patients with tumors 44, 45 , as well as measuring therapeutic benefits of deep brain stimulation 46 . In a phantom study by Yeh et al, the optimized restricted diffusion showed an almost perfect correlation of 0.998 with cell density 1 .…”
Section: Discussionmentioning
confidence: 99%
“…All recognized trajectories were then summed up and pruned by topology-informed pruning (Yeh et al, 2019). A total of 20 pruning iterations was conducted.…”
Section: Topology-informed Pruningmentioning
confidence: 99%
“…This automatic recognition method isolated target pathways and simultaneously excluded irrelevant or false connections that substantially deviated from the known trajectories. After recognition, we further applied topology-informed pruning (Yeh et al, 2019) to eliminate possible false connections. TIP used track density at each voxel to eliminate noisy tracks that failed to form a bundle.…”
Section: Introductionmentioning
confidence: 99%
“…Switching gears to adjuvant techniques, Fernandez-Miranda and colleagues [8] provide an overview of high-definition fiber tractography, an advanced imaging technique that they developed, and have pioneered in neurosurgical planning to optimize functional outcomes in tumor surgery. Yeh and colleagues [9] then tackle the false connection problem in tractography imaging, describing topology-informed pruning (TIP), a method that automatically identifies singular tracts and eliminates them to improve fiber tracking accuracy. Continuing a computational theme, in an original research article, Vakharia and colleagues [10] describe machine learning approaches for predicting trajectories that optimize the extent of mesial temporal lobe ablations during laser interstitial thermal therapy of epilepsy.…”
Section: Evolution Of Traditional Surgeries and Novel Adjuvantsmentioning
confidence: 99%